Analisis Disiplin Kerja Karyawan Pada UD. Putra Tunggal - Siti Uswatun Hasanah; Sampir Andrean Sukoco (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2025)
This study aims to analyze the level of work discipline among employees at UD. Putra Tunggal. Using a descriptive qualitative method, data were collected through structured interviews and validated using source and technique triangulation. The informants consisted of six individuals selected through purposive. Data analysis was conducted through four steps: data collection, condensation, presentation, and conclusion. The findings reveal that employee discipline remains insufficient, influenced by lenient sanctions, lack of rewards, and weak supervision. These issues hinder overall productivity and suggest that stronger enforcement and reward systems are needed.